Factors Affecting Care Leavers in Their Transition to Adulthood: Differences Between National and Migrant Youth in Andalusia (Spain) - Verónica Sevillano-Monje; Ángela Martín-Gutiérrez; Olga Moreno-Fernández; Pilar Moreno-Crespo (Revista de Estudios Sociales)
Both care leavers and non-care leavers go through a transition to adulthood marked by challenges in various aspects of their lives. However, there are significant differences between young nationals and foreign youths who have exited the protection system. This qualitative and socio-biographical study is designed to identify, describe, and interpret the impact of family, educational, employment, and emancipation-related factors that shape the life paths of national and foreign care leavers in Andalusia (Spain). To achieve this, semi-structured interviews were conducted with 53 young people across different provinces of Andalusia. The results showed that, unlike national youths, foreign youths view their families as a source of support and motivation in maintaining and strengthening their life projects. Additionally, foreign youths enrol in more job training courses and with greater motivation compared to their national counterparts. Nevertheless, the study found that preparation for adulthood does not help either national or foreign youths overcome the uncertainty of how to face adult life independently without professional support. It is concluded that socio-educational interventions should, on the one hand, focus on connecting young nationals with the formal support they need to develop and pursue their life projects. On the other hand, these interventions should ensure that both groups of young people receive adequate preparation for the challenges they will face upon reaching adulthood.